Jesús CAÑAS MURILLO, Miguel Ángel LAMA y José ROSO DÍAZ (eds.), «Vicente García de la Huerta y su obra (1734-1787)», Madrid, Visor Libros, 2015, 618 páginas con ilustraciones. - Álvarez Barrientos, Joaquín (Cuadernos de Estudios del Siglo XVIII, 2016)
SIN RESUMEN